HIGHER ORDER THINKING AND CRITICAL THINKING SKILLS OF STUDENTS ON PLANT TISSUE - H Hasruddin; Elisa Lumbantungkup (Jurnal Pelita Pendidikan, 2021)
This research aims to know students' higher order thinking and critical thinking skills on plant tissue topics. The research was conducted in senior high school grade XI Science of SMAN 2 Kisaran,  and the sample was taken by random sampling. The kind of this research is descriptive quantitative. The number of each test, higher-order thinking skills test, and a critical thinking skills test are 30 items. The research results are that the students' higher-order thinking skills of plant tissue topic are at moderate categories. The achievement of students' higher-order thinking skills is at a good level because the value of the higher-order thinking achievement of students in class XI is about 60-69%. The student's critical thinking skills of plant tissue topic is still in less categories. Students' critical thinking skills in this school are at less level because the value of students' higher-order thinking achievement in class XI  is about 50-59%.